Compositional and morphological engineering of mixed cation perovskite films for highly efficient planar and flexible solar cells with reduced hysteresis. (May 2017) - Wang, Changlei; Zhao, Dewei; Yu, Yue; Shrestha, Niraj; Grice, Corey R.; Liao, Weiqiang; Cimaroli, Alexander J.; Chen, Jing; Ellingson, Randy J.; Zhao, Xingzhong; Yan, Yanfa
Abstract: We report on compositional and morphological engineering of mixed methylammonium (MA) and formamidinium (FA) lead triiodide (MA1−x FAx PbI3 ) perovskite absorber layers to produce highly efficient planar and flexible perovskite solar cells (PVSCs) with reduced hysteresis. Incorporation of FA into the MAPbI3 extends the absorption edge of the perovskite to longer wavelengths, leading to enhanced photocurrent of the resultant PVSCs. Moreover, adding a small amount of lead thiocyanate (Pb(SCN)2 ) additive into mixed perovskite precursor solutions significantly enlarges the grain size and prolongs the carrier lifetime, leading to improved device performance. With optimal compositional and morphological engineering, the average power conversion efficiency (PCE) improves from 15.74±0.74% for pure MAPbI3 PVSCs to 19.40±0.32% for MA0.7 FA0.3 PbI3 PVSCs with 3% Pb(SCN)2 additive, exhibiting a high reproducibility and small hysteretic behavior. The best PVSC achieves a PCE of 20.10 (19.85)% measured under reverse (forward) voltage scan. Furthermore, the compositional and morphological engineering allowed the fabrication of efficient flexible PVSCs on indium-doped SnO2 (ITO)/polyethylene terephthalate (PET) substrates, with the best PCE of 17.96 (16.10)% with a V OC of 1.076 (1.020) V, a J SC of 22.23 (22.23) mA/cm 2 and a FF of 75.10 (71.02)% when measured under reverse (forward) voltage scan. Our approach provides an effective pathway to fabricate highly efficient and reproducible planar PVSCs. Graphical abstract: Mixing MAPbI3 precursor with FAPbI3 precursor with the presence of Pb(SCN)2 additive significantly improves crystal quality of mixed cation lead halide perovskite thin films and, therefore, the performances of the resulting perovskite solar cells. The low temperature (100 °C) fabrication process enables us to achieve flexible perovskite solar cells efficiencies up to 17.96%. Highlights: Compositional and morphological engineering leads to 20% efficiency perovskite solar cells. The best-performing flexible perovskite solar cell achieved an efficiency of 17.96%. Mixing formamidinium and methylammonium extends the absorption range to longer wavelength ranges. Pb(SCN)2 additive significantly improves the quality of perovskite films.